2000
DOI: 10.1191/096032700682694242
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for reducing and refining the use of dogs in the regulatory toxicity testing of pharmaceuticals

Abstract: A workshop was held to critically discuss the need for a non-rodent species and the role of the dog in regulatory toxicity testing of pharmaceuticals; to discuss opportunities to reduce and refine the use of dogs in preclinical toxicology; and to identify a number of specific recommendations which could be feasibly achieved to move the process forward. To facilitate a preliminary evaluation of the contribution of dog studies to the risk assessment process, anonymised, unpublished data were provided fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 15 publications
0
22
0
1
Order By: Relevance
“…Some people may assume that dogs are clinically and physiologically closer to humans to demonstrate the need for dogs in drug safety testing is lacking, and that it is possible to achieve a reduction and refinement in dog use without compromising human safety (Broadhead et al, 2000). Since both drug testing and also general biological knowledge have changed considerably during the last 10 years, new comprehensive retrospective evaluations would shed more light on the predictivity, sensitivity and specificity aspects of using dogs in safety evaluations.…”
Section: Canine Models Of Human Inherited Disordersmentioning
confidence: 99%
“…Some people may assume that dogs are clinically and physiologically closer to humans to demonstrate the need for dogs in drug safety testing is lacking, and that it is possible to achieve a reduction and refinement in dog use without compromising human safety (Broadhead et al, 2000). Since both drug testing and also general biological knowledge have changed considerably during the last 10 years, new comprehensive retrospective evaluations would shed more light on the predictivity, sensitivity and specificity aspects of using dogs in safety evaluations.…”
Section: Canine Models Of Human Inherited Disordersmentioning
confidence: 99%
“…The concept of the 'three Rs' (reduction, replacement and refinement) has received considerable attention within safety assessment in recent years (Broadhead et al, 2000;Jenkins and Langley, 2002) and several approaches to reduction and refinement have been proposed. A workshop discussing the possibility of reduction of dog use in toxicology (Broadhead et al, 2000) suggested, for instance, the use of in vitro assays, obtaining more data from safety pharmacology studies and conducting fewer long-term studies. The possibility of better use of data via refined statistical methods, however, was not mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Through this approach, fewer animals are killed after each experiment, and fewer naïve animals -which otherwise would also be killed -need to be bred. There may be limited margin to re-use small laboratory animals because of the limitations for sampling and the need to sacrifice them to obtain tissues, and the low costs for breeding new mice also makes the use of naïve animals for experiments a preferred option, Therefore in practice, reuse of large, non-rodent mammals is more common, in particular in toxicology, pharmacokinetic studies or studies in which telemetry is used [19][20][21][22].…”
Section: Killing Animals In Research -Is It Always Inevitable?mentioning
confidence: 99%